Strategi Pemasaran Online dalam Membentuk Branding Sekolah TK Islam Kencana - Zahrotul Munawwaroh; Nabila Alifia; Muna Mumtazah Syahidah; Muhammad Aidil Kurniawan (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Building a positive perception of educational institutions requires an effective online marketing strategy to maintain its presence among competitors, establish a school brand, and reach a target market aligned with the school's vision and mission. Without a targeted and measurable marketing strategy, the quality of the school's reputation will be compromised. This research aims to describe the online marketing strategy implemented by Kencana Islamic Kindergarten (TK Islam Kencana) in building its school brand. The research approach used a qualitative descriptive method, with data collection techniques through observation, interviews, and documentation studies. The analysis shows that Kencana Islamic Kindergarten actively engages in online marketing to shape and strengthen the school's image (branding). The branding established at Kencana Kindergarten is that of an early childhood education institution with the motto "cheerful, independent, high-achieving, and virtuous." These findings demonstrate that utilizing appropriate digital marketing strategies can enhance branding, enabling educational institutions to compete with their competitors, particularly in gaining public trust and loyalty. This study recommends the need for professional digital content enhancement and regular evaluation of the effectiveness of online promotions in building the school's image.